1990
DOI: 10.1080/03601239009372687
|View full text |Cite
|
Sign up to set email alerts
|

Changes in lipid profiles of liver microsomes of rats following intratracheal administration of DDT or endosulfan

Abstract: The effect of intratracheal administration of DDT (5 mg/100 g body weight) or endosulfan (1 mg/100 g body weight) to rats for three consecutive days, has been studied on liver lipid metabolism. The administration of DDT but not endosulfan significantly increased the liver weight and the microsomal protein contents. Both DDT and endosulfan treatments significantly increased the contents of microsomal phosphatidylcholine (PC), total-free- and esterified cholesterol. The distribution of unsaturated fatty acids of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
14
0

Year Published

1996
1996
2016
2016

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 17 publications
2
14
0
Order By: Relevance
“…The induction of phosphatidylcholine (PC) biosynthesis in lung and liver of rats has been shown following the intratracheal administration of endosulfan (1 mg 100 g -1 body weight) for 3 days. 52 As pointed by Narayan et al, 53 biochemical effects of endosulfan are different in many cases from other organochlorine insecticide. For example, DDT and endosulfan have similar effects on microsomal lipid metabolism, but produce different biochemical manifestations on the secretion of surfactant phospholipids.…”
Section: Biochemical Datamentioning
confidence: 99%
“…The induction of phosphatidylcholine (PC) biosynthesis in lung and liver of rats has been shown following the intratracheal administration of endosulfan (1 mg 100 g -1 body weight) for 3 days. 52 As pointed by Narayan et al, 53 biochemical effects of endosulfan are different in many cases from other organochlorine insecticide. For example, DDT and endosulfan have similar effects on microsomal lipid metabolism, but produce different biochemical manifestations on the secretion of surfactant phospholipids.…”
Section: Biochemical Datamentioning
confidence: 99%
“…Narayan et al have suggested that feeding DDT to rats increased the hepatic phospholipid due to the enhanced synthesis of PC. 10) The administration of such xenobiotics as DDT, PCB and BHT has elevated hepatic lipids and the activity of drug-metabolizing enzymes. 3,10,11) The induction of drug-metabolizing enzymes by xenobiotics is accompanied by the simultaneous induction of PC synthesis.…”
mentioning
confidence: 99%
“…10) The administration of such xenobiotics as DDT, PCB and BHT has elevated hepatic lipids and the activity of drug-metabolizing enzymes. 3,10,11) The induction of drug-metabolizing enzymes by xenobiotics is accompanied by the simultaneous induction of PC synthesis. 10,12) The present study has demonstrated that the hepatic phospholipid level and the proportion of PC were higher in all the DDT-fed groups than in the basal diet-fed group.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Studies document OC exposures in Comarca Lagunera, Mexico City, Puebla, Veracruz (RAPAM, 1997) and the Yaqui Valley in Sonora (Guillette et al, 1998). Such exposures are of great concern, especially since exposure to insecticides has been shown to alter lipid metabolism and produce liver damage in rats (Shakoori et al, 1998;Narayan et al, 1990;Videira et al, 2001;Aldana et al, 1998;Aldana et al, 2001). The objective of our study was to evaluate the potential hepatotoxic effects of insecticide exposure at these levels in rats, using serum biochemical indicators of hepatic damage (transaminases, cholesterol, triglycerides, total protein, and albumin), as well as light and electron microscopy to evaluate microstructure hepatic changes.…”
Section: Introductionmentioning
confidence: 99%